Cardiac performance assessment during cardiopulmonary exercise test can improve the management of children with repaired congenital heart disease. (1st February 2020) - Guirgis, L.; Khraiche, D.; Ladouceur, M.; Iserin, L.; Bonnet, D.; Legendre, A.
Abstract: Background: Children with repaired congenital heart disease (CHD) have impaired maximal aerobic capacity (VO2max). Determining the causes of their VO2max alteration remains challenging. Cardiac output measure using thoracic impedancemetry during cardiopulmonary exercise tests (CPET) can help to understand the determinants of VO2max in children with open-heart repaired CHD. Method: We analyzed CPET in 77 children with repaired CHD. Among them, 55 patients had residual lesions. Patients with repaired CHD were compared with 44 age-matched healthy individuals. Maximal oxygen content brought to capillaries (QO2max) and oxygen muscle diffusion capacity (DO2) were assessed using cardiac output measure, Fick principle and simplified Fick law. Results: In the 55 patients with residual lesion, VO2max, QO2max and DO2 were lower than those of controls (76.1 vs 86% of theoretical value, p < 0.01; 2.15 vs 2.81 L/mn, p < 0.001; 24.7 vs 28.8 ml/min/mmHg, p < 0.05). Decrease in QO2max was due to both impaired stroke volume and chronotropic insufficiency (48 vs 53 ml/m 2 and p < 0.05; 171 vs 185/min p < 0.001). Patients without residual lesion (22/77) had normal VO2max with lower maximal heart rate compensated by higher SV (p < 0.05). Conclusion: Aerobic capacity was normal in children without residual lesions after CHD repair. Patients with residual lesion have impaired VO2max due to both lower central and peripheral determinants. Measuring cardiac performance during CPET allowed a better selection of patients with altered cardiac reserve that can benefit from residual lesion treatment and find the good timing for intervention. Detection of peripheral deconditioning can lead to a rehabilitation program. Highlights: Knowing the central and peripheral causes of VO2max improves patients management. The measurement of cardiac output helps to know the causes of VO2max alteration. Usual CPET parameters failed to differentiate the determinants of VO2max.